2005
DOI: 10.1038/sj.cr.7290372
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and associated malignancies

Abstract: AIDS associated malignancies (ARL) is a major complication associated with AIDS patients upon immunosuppression. Chronically immunocompromised patients have a markedly increased risk of developing lymphoproliferative disease. In the era of potent antiretrovirals therapy (ARV), the malignant complications due to HIV-1 infection have decreased in developed nations where ARV is administered, but still poses a major problem in developing countries where HIV-1 incidence is high and ARV is still not yet widely avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 52 publications
(49 reference statements)
1
36
0
Order By: Relevance
“…The occurrence of HIV-associated malignancies represents a major complication for immunocompromised HIV-infected individuals [43]. Indeed, it has been shown that there is an association between HIV and cancer, particularly anal cancer, Kaposi sarcoma (KS), non-Hodgkin's lymphoma (NHL), primary effusion lymphoma (PEL), primary brain lymphoma and Burkitt's lymphoma (BL) [44].…”
Section: Mtor and Hiv-associated Nephropathymentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of HIV-associated malignancies represents a major complication for immunocompromised HIV-infected individuals [43]. Indeed, it has been shown that there is an association between HIV and cancer, particularly anal cancer, Kaposi sarcoma (KS), non-Hodgkin's lymphoma (NHL), primary effusion lymphoma (PEL), primary brain lymphoma and Burkitt's lymphoma (BL) [44].…”
Section: Mtor and Hiv-associated Nephropathymentioning
confidence: 99%
“…ARLs are often associated to herpes virus-g, EBV or HHV-8 [43]. It is believed that B-cell proliferation stimulated by chronic antigenaemia can result in polyclonal and eventually monoclonal lymphoproliferation [43].…”
Section: Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report of AIDS over 25 years ago, it was noted that there is a close association between HIV infection and the development of a number of cancers (Levine, 2006;Noy, 2006;Pantanowitz et al, 2006;Wood and Harrington, 2005). They include KS, Hodgkin's and high-grade B-cell NHL, anal, and invasive cervical carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Kaposi's sarcoma is the most common malignancies in HIV-infected patients (Wood & Harrington Jr, 2005). Human Herpes Virus-8 has been found to be necessary but not sufficient for its development because other factors such as immunosuppression are also required Laskaris, 2000;Whitby et al, 1995;Wood & Harrington Jr, 2005).…”
Section: Kaposi's Sarcomamentioning
confidence: 99%